(untitled) (Al-Qamar, 2023)
Public accountability in any democratic state appears to be the hallmark of the rule of law and supremacy of the Constitution.[i] This process should equally encompass not only the individuals but also the State institutions because it would ensure the presence of the rule of law in the system wherein both shall be treated alike.[ii] The public accountability of the State institutions is necessary because the resources entrusted and the powers vested to these institutions for utilizing such resources being the sacred trust, must not remain unaccountable in the public interest.[iii] The misuse of public resources will not only blur the 2030 Agenda for Sustainable Development of the United Nations but will also jeopardize the valuable human rights of the citizens. The processes of accountability prevailing in the two most potent contending State institutions in Pakistan, i.e., the army and the judiciary, were examined to assess whether the forms of public accountability present in such cases are sufficient. This paper explored the significant forms of accountability present in the hierarchy of these two institutions. The army was found vertically and financially accountable, making it a disciplined institution. The case study of the judiciary demonstrates that the applicable forms of accountability fail. The judiciary protects citizens’ rights and is directly linked with society. The law-and-order situation in the country is at stake due to the lack of real accountability in this institution. This position has frustrated society and infused a sense of fear, disappointment and insecurity that eventually threatened the 2030 Agenda for Sustainable Development of the United Nations.